Preferences of Physical Education Profiles Among Polish Adolescents - Kuśnierz, Cezary; Zmaczyńska-Witek, Barbara; Rogowska, Aleksandra M. (Frontiers in Public Health, 2020)
The purpose of this study was to examine the association of the preferred profiles of physical education (PE) classes with gender and school level among Polish adolescents. In the cross-sectional survey study, 1,340 Polish students (including 50% of girls) attending middle and high schools, aged between 13 and 19 years, participated. The participants selected one of four preferred profiles of PE classes. The majority (n = 845, 63%) of students participated in PE for “fun–pleasure–entertainment,” whereas only one third of students (n = 419, 31%) preferred “exercise–sweat–fitness” as a profile of PE classes. The preference for “fun–pleasure–entertainment” decreased about 41% for boys and 31% for high school students. A preference for “exercise–sweat–fitness” increased about 56% for men and 31% for high school students. Teachers should comply with students' preferences related to PE profiles, organizing PE classes in more fun-related forms for girls and in more exercise-related forms for boys. The proportions of these two preferred profiles of PE classes should turn across adolescence, increasing exercise-related forms and decreasing those fun-related ones.